The dual role of autophagy in cartilage degradation: from mechanisms to targeted therapeutics - Mei, Jiahua; Zhang, Shenghao; Cui, Xinrong; Yang, Ruiping; Ke, Jin; Cui, Lili; Tan, Lin; Zhu, Shan; Ma, Yunshu (Frontiers in Cell and Developmental Biology, 2026)
Autophagy is a highly conserved cellular degradation and recycling process that plays a pivotal role in maintaining cartilage homeostasis. Normal autophagy is essential for the survival of chondrocytes and the preservation of the extracellular matrix (ECM); however, a decline in autophagic function may lead to the accumulation of damaged organelles and macromolecules, thereby reducing chondrocyte vitality and promoting apoptosis, which in turn contributes to the development of osteoarthritis (OA). This review summarizes the biological processes of autophagy, the interaction between autophagy and cartilage degeneration, as well as the interplay between autophagy and cellular senescence, apoptosis, inflammation, and oxidative stress. Furthermore, we explore key autophagic targets for the regulation of OA and discuss autophagy-targeting therapies, including mTOR inhibitors, AMPK activators, and natural products that target autophagy, along with emerging strategies aimed at modulating autophagy. Finally, the article highlights the challenges in the development of autophagy-targeting drugs for OA treatment and presents important scientific issues that warrant further investigation to guide future research.